Pendampingan Menulis Kreatif untuk Publikasi Artikel Ilmiah di Jurnal Akademik (Covid 19 New Normal) - Rokhyanto Rokhyanto; Titik Purwati; Harun Ahmad (Universitas Pahlawan Tuanku Tambusai, 2022)
The implementation of this service aims to share knowledge and increase potential for teachers in the region, especially in the Gunung Pandak Village area, Kec. Performances, Kab. Malang during the pandemic, to increase knowledge about the world of writing scientific journals. The method follows the drawings of each component of the implementation, including observation, identification of problems related to authentic assessments with partners, as well as plans offered to the implementing team for partner service. Analysis of solving problems faced by teachers, namely: needs analysis related to the renewal of an authentically based assessment system. Authentic assessment needs to be introduced to all components, procedures, and developments in learning, while problem analysis is carried out in the form of teacher abilities related to evaluations that have been carried out through participant activities being able to make articles for academic journals that they can use for the purposes of rank or certification. In the implementation process, it is influenced by various factors, including the appeal of the principal who does not require to write a journal. This activity was carried out by an assistant to MINU teachers while learning to write scientific journal articles, namely the writing movement for teachers to gain more useful knowledge.